Islamic Values in a Multicultural Society: An Analysis of Parenting and Social Integration of Muslim Minorities - Ana Shofiatin; Suraining Rosodor (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This research examines Islamic education parenting and social integration of Muslim minorities in Tanjung Labu Village, Rantau Pulung Sub-district, East Kutai Regency. Using a qualitative method with a case study approach, this research aims to understand the dynamics of Islamic education and social integration strategies in the context of multicultural communities in transmigration areas. Data were collected through participatory observation, in-depth interviews, focus group discussions, and document analysis. The results show that the minority Muslim community in Tanjung Labu Village applies a variety of parenting patterns, from those that tend to be authoritarian in matters of principle to those that are more democratic in other aspects. Social integration efforts are seen in various aspects of life, including education, economy, and culture. Programs such as ‘Friday Taqwa’ in schools and cooperation in farmer groups show positive steps in realizing social integration. However, the research also identified challenges such as the lack of special programs for converts and potential discrimination. The study concludes that efforts to strengthen the social integration of Muslim minorities require a holistic, inclusive, and sustainable approach, involving the active role of the Muslim community and support from various relevant parties. The findings make an important contribution to understanding the complexities of Islamic education and social integration in minority contexts, as well as highlighting the importance of empowering Muslim converts.